2019
DOI: 10.3390/ijerph16224367
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Need Satisfaction and Dissatisfaction on Flourishing among Young Chinese Gamers: The Mediating Role of Internet Gaming Disorder

Abstract: Given the increasing popularity of online game playing, the negative impacts of game addiction on both adolescents and adults attracted our attention. Previous studies based on the self-determination theory have examined the effects of the three basic psychological needs of autonomy, competence, and relatedness on problematic video game playing among Chinese young adults. Yet, as more evidence emerged pointing to the possible relation between need dissatisfaction and higher vulnerability for ill-being and psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 62 publications
(80 reference statements)
1
20
0
Order By: Relevance
“…Moreover, studies have argued that access to related resources encourages individuals' sense of satisfaction. Positive and negative satisfaction can be created with unbiased dimensions of psychosomatic requirements [41]. Moreover, evidence shows that satisfaction and dissatisfaction explain significant factors in IGD [41].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Moreover, studies have argued that access to related resources encourages individuals' sense of satisfaction. Positive and negative satisfaction can be created with unbiased dimensions of psychosomatic requirements [41]. Moreover, evidence shows that satisfaction and dissatisfaction explain significant factors in IGD [41].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Many players without healing skills spent their time indicating safe areas in common chats, while others aimed to spread the disease as much as possible. There have been other cases in the world of similar videogames, linked to bugs that caused real epidemics, even if WoW is one of the most aesthetic in terms of number of players (Hui et al 2019;Li et al 2019a;Sinatra and Szell 2014;Wang et al 2020a). The most complex model developed to deal with a potential COVID-19 pandemic should therefore be SEIR.…”
Section: Resultsmentioning
confidence: 99%
“…Based on two observational studies and one case study conducted in the U.K., they developed a reference model for designing interactive online platforms to intervene DA with peer groups, as well as a process model (i.e., COPE.er) for building a customizable online environment for different disease groups. Echoed with the aforementioned findings on interpersonal risk/protective factors [17][18][19], both interventions involved interpersonal elements.…”
mentioning
confidence: 85%
“…Given the social connection function of the Internet, several studies of this Special Issue highlight the importance of interpersonal factors of IGD/IA. As aforementioned, need dissatisfaction for relatedness was identified as a risk factor of IGD for Chinese young adults by Hui et al [17]. Yang et al [18] found four types of interpersonal stressors that may exacerbate adolescent IGD, which include parental psychological control, physical/verbal abuse by parents, verbal abuse by teachers, and peer/online bullying (N = 2666).…”
mentioning
confidence: 98%
See 1 more Smart Citation